Moral Value in Soul Movie and Its Contribution to Teaching Literature - Fifi Tofiqah Bosavi; Siti Nur'Aini; Nur Hidayat (Wawasan Pendidikan, 2023)
Literature is imaginative works that define human life that society can enjoy, understand, and use. One of the literary forms is a movie. The movie is one form of famous literary work presented visually that contains elements of narrative or story. Using movie also can know a lot of information such as learning the foreign language. A movie is a tool to convey the message depending on the audience because the movie show to the audience through visualization. This research design uses qualitative descriptive. The data sources for this research were taken from a movie is titled Soul. After the researcher has collected all of the data, the researcher will reduce and select the movie for analysis. After that, the researcher will summarize the research result and conclude the research result. This study analyzed the types of moral value, the most dominant moral value, and the contribution to teaching literature. The total numbers of types of moral value in Soul movie are 16. They are self-confident and potential, helping other, respect, responsibilities, courage, love and affection, and appreciation. The most dominant moral value in Soul movie is self-confidence and potential, and the total numbers are 6 types of moral value.